Dental fear among the school going-children of Taif, Saudi Arabia - Alotaibi, Khalid S.; Alzahrani, Turki A.; Holenarasipur, Amith V. (International Journal Of Community Medicine And Public Health, 2024)
Background: Dental fear is a phenomenon that is founded in most of the populations weather the individual is a child or an adult. Objectives were to understand the aspects and the percentages of dental fear among school going children and determine the nature of dental fear in children and to assess the prevalence of dental fear in school going children of Taif city, Suadi Arabia. Methods: Participants were the school children of Taif city, Saudi Arabia. The Children's fear survey schedule – dental subscale (CFSS-DS) was used that was obtained from an online article with a similar topic and it was in Arabic language. The questionnaire forms were distributed to the school going children and responses collected from them at the end of each school visit. Results: The study included 303 school-aged children. It was discovered that the statement with the highest mean indicating that the child is very afraid was: "Are you afraid of the dentist's drill?" (1.84±1.17). The statement with the lowest mean indicated that the child was not afraid: "Are you afraid of people in white clothes?" (1.18±0.69). The mean CFSS-DS score was 22.05±9.44. According to the CFSS-DS score classification cutoff, 19 (6.3%) of the studied children had dental anxiety. Conclusions: The most feared aspect was the dentist drilling followed and the least feared aspect was people in white coat, with a prevalence of 6.3% of dental anxiety among studied children.